a Community health nursing : caring in action - Hitchcock, Janice E.; Schubert, Phyllis E.; Thomas, Sue A (Clifton Park, NY : Thomson/Delmar Learning, 2003)
A concise, innovative community health nursing book, Community Health Nursing: Caring in Action, 2E presents all major community and public health topics. This revised edition emphasizes the roles and responsibilities of the community and public health nurse, with special emphasis on international, multicultural, poverty, alternative healing modalities and other emerging themes. A new full-color design and many photographs and illustrations further help bring this edition to life. New edition on The use of full color makes the identification of the pedagogical and special features easy, the illustration come alive, and provides the student with a visually appealing experience.
New chapter on Integrative Health Care Perspectives discusses the increasing use of integrative therapies, an overview of the thought traditions and perspectives of health care, nursing theory and the use of integrative therapies in community health nursing and its implications for practice. New chapter on Quality Management explores the concept of quality, the historic development of quality in health care, the use of evaluative models in quality management, and the implications it has in community health nursing.
INURSING AND CARING IN THE COMMUNITY -- HEALTH CARE: NATIONAL AND INTERNATIONAL PERSPECTIVES -- FOUNDATIONS OF COMMUNITY HEALTH NURSING -- CARING FOR THE COMMUNITY -- CARING FOR INDIVIDUALS AND FAMILIES IN THE COMMUNITY -- CARING FOR VULNERABLE POPULATIONS.
Includes bibliographical references and index.
System requirements for accompanying CD-ROM: Windows 95 or newer
1
Keywords: Community health nursing; Public health nursing; Community Health Nursing; Public Health Nursing